El manejo del Celular y su Impacto como medio de comunicación de uso masivo, en los estudiantes del tercer año de bachillerato de la Unidad Educativa Diez de Agosto perteneciente al Cantón Montalvo, Provincia Los Ríos, en el periodo lectivo 2015-2016 - Camacho Chiriguaya, Jaime José (2016)
This research studies the management of the cell phone and its impact as a means of mass communication, in the third year of high school students of the Education Unit Diez de Agosto belonging to Montalvo, Los Ríos Province, in the academic period 2015-2016, Considering that the cellular is part of the personalized entertainment for the young in this case the students that are the reason for this investigation, an exploratory explanatory character analysis was used, which seeks to explain the implications of this phenomenon in the field of communication, socied-cultural, socied educative, For being a classic in the communicative access of young people who are developing in a new technological generation, in which it tries to increase new platforms as well as communication strategies and facilitate access to information. Young people today have varieties of options to give, receive, hear and see all that surrounds them in a technological communicative era, through the surveys and observation made to the students of the Educational Unit Diez de Agosto the advantages were determined , Disadvantages of the use of the mobile device according to the needs of the students, which allowed to demonstrate the impact generated by this topic of study in the social, educational and personal environment, analyzing the institutional environment to socialize as they feel with the new technologies implemented , To seek personal empathy with the use of the cell phone in educational tasks and daily activities, ceasing to be considered as a social status, since this subject is an object of study, seeking to include technological devices that help improve Teaching methods and labor competitiveness. This study allows later to improve the processes of training of the young people and adolescents within an educational institution that affects the learning environments, therefore it is necessary to focus on the interest of implementing ideas that point to the possible solutions of the subject addressed, to generate A change both student and community, at the moment of communicating with the speed that is nowadays required, give an appropriate use to obtain their benefits and report quickly but knowing the proper way to navigate in time and space with the greatest responsibility